Pengembangan Aplikasi Mobile untuk Peningkatan Layanan Kesehatan di Klinik Menggunakan Metode Waterfall: Studi Kasus Klinik XYZ - Muhammad Nurwegiono (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
In this digital era, patients expect ease of access and transparency in healthcare services. Klinik XYZ, currently using conventional methods, faces challenges in meeting these expectations, such as long queues, incomplete information, and difficulties in scheduling appointments with doctors. This study aims to develop a mobile application to enhance service quality at Klinik XYZ. The method used is Waterfall, involving the stages of needs analysis through observation and interviews, system design, coding, and testing. The findings show that the developed application can provide essential features such as doctor profiles, doctor schedules, appointment scheduling, service selection, ratings, news, and health tips. This application successfully improves the efficiency and quality of services at Klinik XYZ by reducing waiting times and providing a better user experience. The implications of this study indicate that integrating mobile technology into healthcare services can significantly enhance patient satisfaction and the operational effectiveness of the clinic. Arifin, M. N., & Siahaan, D. (2020). Structural and Semantic Similarity Measurement of UML Use Case Diagram. Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 11(2), 88. https://doi.org/10.24843/lkjiti.2020.v11.i02.p03 Febriyanti, N. M. D., Sudana, A., & ... (2021). Implementasi Black Box Testing pada Sistem Informasi Manajemen Dosen. Jurnal Ilmiah …, 2(3). http://download.garuda.kemdikbud.go.id/article.php?article=3457876&val=30165&title=Implementasi Black Box Testing pada Sistem Informasi Manajemen Dosen Haerani, R., Hendriyati, P., Nugroho, P. A., & Lukman, M. (2023). Waterfall Model Implementation in Information Systems Web Based Goods Delivery Service. JURTEKSI (Jurnal Teknologi Dan Sistem Informasi), 9(3), 501–508. https://doi.org/10.33330/jurteksi.v9i3.2267 Lee Ventola, C. (2014). Mobile devices and apps for health care professionals: Uses and benefits. P and T, 39(5), 356–364. Luxton, D. D., Kayl, R. A., & Mishkind, M. C. (2012). MHealth data security: The need for HIPAA-compliant standardization. Telemedicine and E-Health, 18(4), 284–288. https://doi.org/10.1089/tmj.2011.0180 Martínez-Pérez, B., De La Torre-Díez, I., & López-Coronado, M. (2013). Mobile health applications for the most prevalent conditions by the world health organization: Review and analysis. Journal of Medical Internet Research, 15(6). https://doi.org/10.2196/jmir.2600 Nurbaiti Oktaviani, S., Fikri Aziz, C., & Maula Sulthon, B. (2022). Analisa UI/UX Sistem Informasi Penjualan Berbasis Mobile Menggunakan Metode Prototype. KLIK: Kajian Ilmiah Informatika Dan Komputer, 2(6), 225–233. https://doi.org/10.30865/klik.v2i6.401 Rambe, B. H., Pane, R., Irmayani, D., Nasution, M., Munthe, I. R., Ekonomi, F., & Bisnis, D. (2020). UML Modeling and Black Box Testing Methods in the School Payment Information System. Jurnal Mantik, 4(3), 1634–1640. https://iocscience.org/ejournal/index.php/mantik